Mental and Physical Health and Hygienic, Nutritional and Daily Habits during Quarantine in COVID-19 Pandemic - Dillon, Carol (2020)
Introduction: The outbreak of the new coronavirus (COVID-19) was declaredas a pandemic by the World Health Organization in March 2020. TheArgentinian government adopted a preventive social isolation and lockdownstrategy as an exceptional measure in this critical world context. This lockdownstrategy has kept a large number of people in isolation and affectedmany aspects of people?s lives. Objective: To describe the physical and mentalhealth status and possible changes in hygienic, nutritional and, daily habitsduring quarantine in the COVID-19 pandemic. Materials and Method: Anonline anonymous survey was sent to the general population of Buenos Airescity, 434 people answered the questionnaire. Results: Fifty-one percent ofrespondents were between 40 and 70 years old. Most respondents were female(75.8%) and had higher education (62.2%). Thirty point eight percent had apre-existing disease and in 50.7% of these cases, the usual symptoms experiencedby respondents remained unchanged. The onsets of anxiety (38.2%),depression symptoms (27.9%), sleep disorders (20.5%), and irritability(27.2%) were reported during the isolation period. Also, changes in eatinghabits (55.5%) were reported. Significant improvement was reported in personalhygiene (80.2%) and home cleaning (81.3%) habits. It was also observedthat despite the isolation some people continued doing physical activity.Conclusions: Respondents did not report significant changes in the symptomsof their preexisting diseases and had a positive mindset towards personalhygiene and home cleaning. Also, reported continuity in physical activity during isolation. However, the onset of psychiatric symptoms such as anxiety, depression, irritability and sleep problems, and, changes in eating habits were observed during the quarantine.